PENGALAMAN GURU IPA DALAM MENGEMBANGKAN DAN MENGGUNAKAN MEDIA PEMBELAJARAN: STUDI KUALITATIF DI SEKOLA MENENGAH PERTAMA - Hamrulla P; Citra Rosalyn Anwar; Herawan Hisanan (STKIP Subang, 2026)
This study aims to describe teachers' experiences in developing instructional media for science teaching in junior high schools. The focus of the study includes the teachers' media development process, the obstacles encountered during media development and use, and the contribution of these experiences to the implementation of science teaching. This study employed a qualitative approach with a descriptive approach. The informants consisted of three science teachers. Data were collected through in-depth interviews, observation, and documentation, then analyzed using data reduction, data presentation, and conclusion drawing techniques. Data validity was achieved through source and method triangulation. The results show that teachers developed instructional media by considering learning objectives, student characteristics, and the material being taught. The media used included PowerPoint, instructional videos, student worksheets (LKPD), Canva, and other game applications. Challenges faced included limited time, supporting resources, and diverse student abilities. Teachers overcame these obstacles through the use of various learning resources, training, and collaboration with fellow teachers. These experiences positively contributed to the implementation of science teaching, particularly in increasing student engagement, motivation, and understanding during the learning process.